Community’s Perception and Attitude towards People with Epilepsy in Ethiopia - Wubalem Fekadu; Tesfa Mekonen; Shemelash Bitew; Tefera Chanie Mekonnen; Melak Menberu; Seble Shewangizaw (Behavioural Neurology)
Introduction. Most people with epilepsy suffer from a dual burden. In one hand, they struggle with the symptoms and disabilities on the other hand from misconceptions and stigma associated with it. But there are no recent studies which assess the community’s perception and attitude. Objective. To assess the perception and attitude of the community towards people with epilepsy and identify associated factors. Methods. A community-based cross-sectional study was conducted in South Ethiopia from a total of 701 participants. Data were collected with face to face interview using a structured questionnaire developed based on the Health Belief Model (HBM). Data were presented with frequencies, tables, and figures. Univariate and multivariable logistic regression was done to identify significantly important variables. The presence of association was presented by odds ratio and 95% confidence interval. Ethical clearance was obtained from Wolaita Sodo University. Results. The most frequently mentioned perceived causes for epilepsy were stress (91%), substance use (61.8%), and bad spirit (49.8%) while loss of consciousness and falling (80.7%) and sleep problems (78%) were considered symptoms of epilepsy. Only 13.1% of the participants think that they may be susceptible for epilepsy. Six hundred sixty (94.2%) participants will not employ a person with epilepsy while only 47 (6.7%) of the participants will allow a family member to marry a person with epilepsy. In multivariable analysis, understanding the illness as a medical problem was associated with perceived susceptibility and perceived benefit of modern treatment was significantly associated with having a current medical problem. Conclusions. The knowledge about the cause, possible susceptibility, better treatment options, and attitude of the participants were similar to other low-income settings. The negative attitude was high and multidimensional. All stakeholders must work to increase awareness about the cause, symptoms, and treatment options for epilepsy and to decrease the negative attitude of the community.